44‐2: Separation Process using Commercially Available Polyimide or Acrylic with Linear Laser. Issue 1 (2nd June 2017) - Idojiri, Satoru; Ohno, Masakatsu; Sato, Masataka; Ikezawa, Naoki; Yasumoto, Seiji; Kumakura, Kayo; Adachi, Hiroki; Okazaki, Kenichi; Yamazaki, Shunpei
Abstract : The use of a buffer layer in a separation layer containing commercial polyimide or acrylic allows normal laser separation without using special laser irradiation, even if foreign particles (approximately 1 mmΦ) are attached to a glass substrate. A linear laser used for the crystallization of low‐temperature polysilicon can be used.